A bcr-3 isoform of RARα-PML potentiates the development of PML-RARα-driven acute promyelocytic leukemia - Pollock, Jessica L. (The National Academy of Sciences, 1999)
Acute promyelocytic leukemia (APML) most often is associated with the balanced reciprocal translocation t(15;17) (q22;q11.2) and the expression of both the PML-RARα and RARα-PML fusion cDNAs that are formed by this translocation. In this report, we investigated the biological role of a bcr-3 isoform of RARα-PML for the development of APML in a transgenic mouse model. Expression of RARα-PML alone in the early myeloid cells of transgenic mice did not alter myeloid development or cause APML, but its expression significantly increased the penetrance of APML in mice expressing a bcr-1 isoform of PML-RARα (15% of animals developed APML with PML-RARα alone vs. 57% with both transgenes, P < 0.001). The latency of APML development was not altered substantially by the expression of RARα-PML, suggesting that it does not behave as a classical “second hit” for development of the disease. Leukemias that arose from doubly transgenic mice were less mature than those from PML-RARα transgenic mice, but they both responded to all-trans retinoic acid in vitro. These findings suggest that PML-RARα drives the development of APML and defines its basic phenotype, whereas RARα-PML potentiates this phenotype via mechanisms that are not yet understood.